The Comparison of Effectiveness of Gestalt Therapy and Acceptance and Commitment Therapy on Emotional Schemas and Post-Traumatic Growth - Afsaneh Abidizadegan; Seyed Asghar Mousavi; Mohammad Narimani (Iranian Journal of Educational Research)
Objective: The aim of this research was to compare the efficacy of Gestalt therapy and acceptance and commitment therapy in enhancing emotional schemas and post-traumatic growth in adolescent girls diagnosed with post-traumatic stress disorder. Methods: Employing an experimental design, the study was carried out with a pretest-posttest approach involving a control group, followed by a two-month follow-up period. Using purposive sampling, 60 girls were selected to participate, divided into two experimental groups (each consisting of 20 girls) and a control group (20 girls). The experimental groups received either Gestalt therapy (10 sessions of 90 minutes each) or ACT (10 sessions of 90 minutes each), while the control group did not undergo any intervention and remained on a waiting list. Data collection involved the application of the PTSD Symptom Scale-Interview (Foa et al., 1993), Leahy's Emotional Schemas Scale (2002), and the Posttraumatic Growth Inventory (PTGI) by Tedeschi and Calhoun (1996). Data analysis was conducted using repeated measures analysis of variance and Bonferroni test. Results: The findings revealed that both therapeutic approaches exhibited a significant impact on emotional schemas and post-traumatic growth in adolescent females with post-traumatic stress disorder during the post-test and follow-up assessments (P<0.05). Moreover, Gestalt therapy demonstrated more pronounced enhancements in emotional schemas, whereas ACT showed greater improvements in post-traumatic growth (P<0.05). Conclusions: Consequently, it can be deduced from the outcomes of this investigation that Gestalt therapy and ACT present viable treatment options for enhancing emotional schemas and post-traumatic growth among adolescent females grappling with post-traumatic stress disorder within therapeutic environments.